2009
DOI: 10.1146/annurev.immunol.021908.132532
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Activation of Macrophages: An Immunologic Functional Perspective

Abstract: Macrophages are innate immune cells with well-established roles in the primary response to pathogens, but also in tissue homeostasis, coordination of the adaptive immune response, inflammation, resolution, and repair. These cells recognize danger signals through receptors capable of inducing specialized activation programs. The classically known macrophage activation is induced by IFN-gamma, which triggers a harsh proinflammatory response that is required to kill intracellular pathogens. Macrophages also under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

54
2,208
4
29

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 2,416 publications
(2,339 citation statements)
references
References 166 publications
54
2,208
4
29
Order By: Relevance
“…The marker is highly expressed on plasma membrane processes and efficiently reveals potential interactions with neighbouring cells in tissues, as demonstrated in immunocytochemical studies by David Hume, Hugh Perry and others (reviewed in [2]; see also www.macrophages.com). Unlike the Mac-1 antigen identified by Springer et al [3], F4/80 is absent on neutrophils; unlike the pan-macrophage antigen, CD68 [4], it is dim or absent on selected Mf populations such as splenic marginal zone Mfs and osteoclasts. Subsequent cloning by Andrew McKnight et al [5] revealed that F4/80 is a seven-span transmembrane molecule with a large extracellular domain consisting of multiple EGF modules, and is related to another myeloid antigen, CD97, described by Jörg Hamann et al [6].…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…The marker is highly expressed on plasma membrane processes and efficiently reveals potential interactions with neighbouring cells in tissues, as demonstrated in immunocytochemical studies by David Hume, Hugh Perry and others (reviewed in [2]; see also www.macrophages.com). Unlike the Mac-1 antigen identified by Springer et al [3], F4/80 is absent on neutrophils; unlike the pan-macrophage antigen, CD68 [4], it is dim or absent on selected Mf populations such as splenic marginal zone Mfs and osteoclasts. Subsequent cloning by Andrew McKnight et al [5] revealed that F4/80 is a seven-span transmembrane molecule with a large extracellular domain consisting of multiple EGF modules, and is related to another myeloid antigen, CD97, described by Jörg Hamann et al [6].…”
Section: Introductionmentioning
confidence: 63%
“…Mononuclear phagocytes constitute a system characterised by considerable diversity. Indeed, two major themes have emerged in recent macrophage investigations: their heterogeneity in different tissue environments and phenotypic plasticity in various physiologic and pathologic states [2][3][4][5]. Macrophages contribute to tissue homeostasis by the clearance of effete and injured host components and to defence against infection by phagocytosis and microbial killing.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they have strongly enriched integrin complexes (including integrins alpha‐5, alpha 6, beta‐1, beta‐2, and beta‐5) and express higher levels of lectins such as mannose receptor 1 (MRC1), galectins 1, 3, 8, and 9 as well as chitinase‐like protein 3 (Chil3/Ym1) and Sialoadhesin (Siglec1). Interestingly, BMDMs express also four times more Clec10a (Mgl1) which has been used with MRC1 and Ym1 as markers for alternatively activated macrophages 22. RAW 264.7, on the other hand, express higher levels of Clec4e (Mincle), Clec4a (Dcir), and Clec7a (Dectin 1), as well as a fourfold higher amount of interferon‐γ receptor, suggesting that the basal activation state of RAW 264.7 cells is considerably more proinflammatory compared to BMDMs.…”
mentioning
confidence: 99%
“…While this article focuses on mammalian (mainly human) Hsp60 proteins, much of our information of the signalling properties of Hsp60 proteins have come from the study of bacterial proteins; as this may have relevance to the properties of the human protein it will be briefly discussed. A major area of current research in immunology and infectious diseases research is the activation status of human or rodent monocytes [48]. Macrophages exposed to interferon gamma (IFNγ) or to LPS are called classically-activated macrophages and are 'activated' in a way that promotes the presentation of antigens to T lymphocytes (e.g.…”
Section: Hsp (Chaperonin)60mentioning
confidence: 99%
“…upregulation of MHC class II proteins) or kills bacteria (production of reactive oxygen radicals). However, it has been found in more recent years that other signals can induce a range of other macrophage activation states that have been termed alternative activation [48]. The finding that M. tuberculosis Hsp60.2 protein stimulated the production of pro-inflammatory cytokines suggested that it was inducing a classically-activated state.…”
Section: Hsp (Chaperonin)60mentioning
confidence: 99%